LOUIS ALTHUSSER: MARXIS STRUKTURAL - Oktovianus Kosat (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
Louis Althusser has been called a structuralist or precisely as a structural marxist. Althusser himself does reject the name structuralist, but in some terms he uses, such as structure, structural, anti-humanism, anti-historisism, makes himself close to the structuralistic terminology. The emphasis it should have on his thinking of theoretical humanism was the attempt to avoid any misconception that he was opposing humanism, emphasizing human dignity and human rights. Though he merely rejected the stand that made man the center of history and the center of reality. For Althusser, this establishment was a humanism to the theory of Marx and Lenin, of history.